2016
DOI: 10.1038/ncomms11772
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia infections in natural Anopheles populations affect egg laying and negatively correlate with Plasmodium development

Abstract: The maternally inherited alpha-proteobacterium Wolbachia has been proposed as a tool to block transmission of devastating mosquito-borne infectious diseases like dengue and malaria. Here we study the reproductive manipulations induced by a recently identified Wolbachia strain that stably infects natural mosquito populations of a major malaria vector, Anopheles coluzzii, in Burkina Faso. We determine that these infections significantly accelerate egg laying but do not induce cytoplasmic incompatibility or sex-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
215
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(226 citation statements)
references
References 53 publications
5
215
3
3
Order By: Relevance
“…gambiae in additional villages in Burkina Faso 71 and Anopheles species collected in Illinois, USA 72 . Our study describing resident Wolbachia strains in numerous species of Anopheles malaria vectors also highlights the potential for Wolbachia to be influencing malaria transmission, as postulated by previous studies 39, 40, 73 . Although no significant correlation was present for malaria and Wolbachia prevalence in the 128 An.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…gambiae in additional villages in Burkina Faso 71 and Anopheles species collected in Illinois, USA 72 . Our study describing resident Wolbachia strains in numerous species of Anopheles malaria vectors also highlights the potential for Wolbachia to be influencing malaria transmission, as postulated by previous studies 39, 40, 73 . Although no significant correlation was present for malaria and Wolbachia prevalence in the 128 An.…”
Section: Discussionsupporting
confidence: 77%
“…gambiae s.s. individuals from DRC, we only detected co-infections in two individuals compared to 13 and 15 individuals infected only with Wolbachia or P. falciparum , respectively. As the majority (77%) of samples had neither detectable Wolbachia resident strains or P. falciparum, a larger sample size would be needed to determine if there is a correlation, as shown previously in both Burkina Faso 73 and Mali 40 . The infection prevalence of resident Wolbachia strains in An.…”
Section: Discussionmentioning
confidence: 99%
“…arabiensis that is absent in Gabon (Table 1) . By PCR amplification of a 16S rRNA fragment (Shaw et al, 2016), we found 70 Wolbachia-positive specimens that belonged to 16 different Anopheles species, distributed throughout the country (Figure 1, Table S1). When considering only species with more than 10 screened individuals, we observed that Wolbachia infection was commonly lower than 15% (11/13), as observed in other arthropods (Duron et al, 2008;Zug & Hammerstein, 2012).…”
Section: Wolbachia Naturally Infects a Large Number Of Anopheles Spmentioning
confidence: 99%
“…Reshuffling these modules could create proteins with altered subcellular localization patterns or novel target specificities (Gerth & Bleidorn, ). Wolbachia have attracted enormous interest from a public health point of view (Servick, ; Waltz, ), because they have a strong impact on the propagation of infectious diseases of humans by affecting the viral amplification and reproduction of disease vector insects (Burt, ; Caragata, Dutra, & Moreira, ; Shaw et al., ). Considering the fact that Wolbachia are not currently amenable to genetic modifications, manipulations of host physiology with molecular resources derived from Wolbachia would be a feasible approach for the control of vector insects.…”
Section: Discussionmentioning
confidence: 99%